'Even though you hate everything that's going on, you know they are safer at home': The role of Aboriginal and Torres Strait Islander families in methamphetamine use harm reduction and their own support needs. (31st May 2022) - Gendera, Sandra; Treloar, Carla; Reilly, Rachel; Conigrave, Katherine M.; Butt, Julia; Roe, Yvette; Ward, James
Abstract: Introduction: First Nations people who use methamphetamine are overrepresented in regional and remote Australia and more likely to turn to family for support. This can place strain on families. The support needs of family members of individuals using methamphetamine are poorly understood. Methods: We conducted 19 focus groups and seven interviews with mostly First Nations community, family members and service providers. In total, 147 participants across six sites participated as part of a larger study investigating First Nations perspectives of how to address methamphetamine use and associated harms. We applied a social and emotional wellbeing framework to examine support needs and role of family in mitigating methamphetamine harms. Results: Findings highlighted the importance of families in providing support to people using methamphetamine and in reducing associated harms, often without external support. The support provided encompassed practical, social, emotional, financial, access to services and maintaining cultural connection. Providing support took a toll on family and negatively impacted their own social and emotional wellbeing. Discussion and Conclusions: First Nations families play an important and under‐recognised role in reducing methamphetamine‐related harms and greater efforts are required to support them. Professional resources are needed to deal with impacts of methamphetamine on families; these should be pragmatic, accessible, targeted and culturally appropriate. Support for families and communities should be developed using the social and emotional wellbeing framework that recognises wellbeing and healing as intrinsically connected to holistic health, kinship, community, culture and ancestry, and socioeconomic and historical influences on peoples' lives.